Identification of Eimeria tenella sporozoite immunodominant mimotopes by random phage-display peptide libraries–a proof of concept study - Juárez-Estrada, Marco A.; Tellez-Isaias, Guillermo; Graham, Danielle M.; Laverty, Lauren; Gayosso-Vázquez, Amanda; Alonso-Morales, Rogelio A. (Frontiers in Veterinary Science, 2023)
Coccidiosis, caused by parasites of numerous Eimeria species, has long been recognized as an economically significant disease in the chicken industry worldwide. The rise of anti-coccidian resistance has driven a search for other parasite management techniques. Recombinant antigen vaccination presents a highly feasible alternative. Properly identifying antigens that might trigger a potent immune response is one of the major obstacles to creating a viable genetically modified vaccine. This study evaluated a reverse immunology approach for the identification of B-cell epitopes. Antisera from rabbits and hens inoculated with whole-sporozoites of E. tenella were used to identify Western blot antigens. The rabbit IgG fraction from the anti-sporozoite serum exhibited the highest reactogenicity; consequently, it was purified and utilized to screen two random Phage-display peptide libraries (12 mer and c7c mer). After three panning rounds, 20 clones from each library were randomly selected, their nucleotide sequences acquired, and their reactivity to anti-sporozoite E. tenella serum assessed. The selected peptide clones inferred amino acid sequences matched numerous E. tenella proteins. The extracellular domain of the epidermal growth factor-like (EGF-like) repeats, and the thrombospondin type-I (TSP-1) repeats of E. tenella micronemal protein 4 (EtMIC4) matched with the c7c mer selected clones CNTGSPYEC (2/20) and CMSTGLSSC (1/20) respectively. The clone CSISSLTHC that matched with a conserved hypothetical protein of E. tenella was widely selected (3/20). Selected clones from the 12-mer phage display library AGHTTQFNSKTT (7/20), GPNSAFWAGSER (2/20) and HFAYWWNGVRGP (8/20) showed similarities with a cullin homologue, elongation factor-2 and beta-dynein chain a putative E. tenella protein respectively. Four immunodominant clones were previously selected and used to immunize rabbits. By ELISA and Western blot, all rabbit anti-clone serums detected E. tenella native antigens. Thus, selected phagotopes 2 This is a provisional file, not the final typeset article contained recombinant E. tenella antigen peptides. Using antibodies against E. tenella sporozoites, this study demonstrated the feasibility of screening Phage-display random peptide libraries for true immunotopes. In addition, this study looked at an approach for finding novel candidates that could be used as an E. tenella recombinant epitope-based vaccine.